T cells expressing NKG2D chimeric antigen receptors efficiently eliminate glioblastoma and cancer stem cells. Issue 1 (9th July 2019) - Yang, Dong; Sun, Bin; Dai, Hongjiu; Li, Wenxuan; Shi, Lan; Zhang, Peixian; Li, Shirong; Zhao, Xudong
Abstract : Background: Traditional therapies fail to cure most glioblastoma patients and the 5-year survival rate is less than 10%, highlighting need for new therapeutic approaches. The natural killer group 2 member D ligands (NKG2DLs) are highly expressed in glioblastomas and are considered promising targets for chimeric antigen receptor (CAR) T-cell therapy. The aim of this study was to investigate the effect of NKG2D-expressing CAR-T cells on glioblastomas and glioblastoma stem cells. Methods: The expression of NKG2DLs was analyzed by flow cytometry and immunohistochemistry. NKG2D-BBz CAR, containing the extracellular domain of NKG2D, was constructed and delivered into T cells by lentiviral particles. In vitro cytotoxicity of the CAR-T cells was assessed by flow cytometry. Release of cytokine, perforin and granzyme B was quantified using enzyme-linked immunosorbent assay kits. The therapeutic efficacy of NKG2D-BBz CAR-T cells in vivo was evaluated using subcutaneous tumor models. The safety of the CAR was analyzed by investigating the effects on proliferation, apoptosis, and karyotype. Results: Our data confirmed the high expression of NKG2DLs in human glioblastoma cells, cancer stem cells, and tumor samples. Further, the NKG2D-BBz CAR-T cells efficiently lysed glioblastoma cells and cancer stem cells in vitro and produced high levels of cytokines, perforin, and granzyme B. The CAR-T cells markedly eliminated xenograft tumors in vivo and did not exhibit significant treatment-related toxicity in the treated mice. The CAR expression also did not exert any obvious effects on cell proliferation, apoptosis, and genomic stability. Conclusion: Our findings demonstrated that NKG2D CAR-T cells targeted glioblastoma cells and cancer stem cells in an NKG2D-dependent manner, supporting the use of CAR-T therapy in glioblastoma therapeutic strategies.